Refractory Port Wine Stains (PWS): Long Pulsed Alexandrite Laser as an Option - Seirafi, Hassan; Farnaghi, Farshad; Ehsani, Amirhooshang; Asghari Shiekhi, Majid; Gholamali, Fatemeh; Noormohammadpour, Pedram (Journal of Lasers in Medical Sciences, 2012)
INTRODUCTION: Port wine stains (PWS) are congenital vascular malformations. Pulsed dye laser (PDL) is the treatment of choice till now, although many lesions do not respond completely. One of possible options is long pulsed alexandrite laser. Some literatures confirmed its efficacy. The aim of the present study is to determine the efficacy of this laser as an option in treating refractory PWS in Iranian patients. METHODS: Patients with refractory PWS lesions that did not respond to at least six PDL sessions were included if they had no history of Isotretinoin consumption in past year, history of keloid or hypertrophic scar formation, active infection in laser site and if they were not pregnant. All patients signed an informed consent. Alexandrite laser with fluencies from 36-40J/Cm2, 12 mm spot size, 3 ms pulse duration and dynamic cooling device tuned to 50/50 ms was used in three successive sessions to treat lesions. All patients photographed before each session and after 8 weeks from the last sessions. Then, pictures were rated by two blinded dermatologist rater to determine degree of response based of visual analog scaling from score 1(below 25% response) to score 4 (more than 75% response). RESULTS: A total of 20 patients comprised of 12 males and 8 females with mean age of 23 years were included. 35% (7 patients) had score of 1, 35% (7 patients) had score of 2, 25% (5 patients) had score of 3 while one patient (5%) reached score 4. No serious side effect was observed. There was no significant relationship with age, gender and size of lesions and response rate. CONCLUSION: It seems that considering a conservative approach, long pulsed alexandrite laser may be an effective option in treating refractory PWS lesions. Although future studies with higher sample size using higher fluences are required to confirm these results.